PENDEKATAN RASIO OUTPUT INPUT UNTUK PENGUKURAN PRODUKTIVITAS PERUSAHAAN DI UD X - M. Imron Mas'ud (Universitas PGRI Madiun, 2022)
This study aims to measure the productivity level of plastic ore processing companies using the PE 1+ type of input output ratio approach at UD. X which is located in Pasuruan Regency. This research was carried out considering the current amount of plastic waste that continues to grow and the very rapid development of the plastic ore processing industry today is marked by the emergence of new industries and the development of small, medium and large scale plastic ore processing industries, so that companies are automatically demanded to be more efficient. efficient and effective so that it leads to a healthy, productive and competitive company, one of which is by measuring the level of productivity with the Output Input Ratio approach. The results showed that the company's total productivity was 1.0323. This means that each use of input (I) totals Rp. 1,032,300 rupiah produces a total output (O) of Rp 1,014,600 rupiah.